Mesiodistal tip expression of mandibular anterior teeth in patients with mandibular incisor extraction treated with Invisalign aligners - Truong, Laura; Weir, Tony; Nguyen, Hien; Freer, Elissa; Ong, Desmond (American journal of orthodontics and dentofacial orthopedics, 2024)
Extraction of a single mandibular incisor may be prescribed in conjunction with clear aligner orthodontic treatment. The accuracy of therapeutic mesiodistal tooth positioning for the remaining mandibular anterior teeth for such patients has not been comprehensively evaluated. This retrospective study compared the predicted and achieved mesiodistal tooth movements in the mandibular anterior region for patients treated with Invisalign (Align Technology, Santa Clara, Calif), along with the influence of aligner attachments and the frequency of aligner change. A sample of 83 subjects who had undergone Invisalign treatment with a single mandibular incisor extraction was collected from an existing database. The pretreatment tooth positions, the predicted mesiodistal tooth movement, and the achieved outcomes were measured for the remaining mandibular anterior teeth using Geomagic Control X metrology software (3D Systems, Rock Hill, SC). The predicted and achieved mesiodistal tip movements were analyzed and compared. Regression analysis revealed significant differences (P <0.001) between the predicted and achieved mesiodistal tooth positioning for incisors and canines. For every degree of predicted incisor mesiodistal tip, 78.89% of this tip was achieved (R2 = 0.4901). For every degree of predicted canine tip, 54.16% was clinically expressed (R2 = 0.5965). The accuracy of mesiodistal tip expression was not significantly affected by the prescribed number of aligners, 1-week vs 2-week aligner change protocols, or the presence of attachments (P >0.05). In addition, incisors were less likely to express the correct direction of the mesiodistal tip predicted than canines (P = 0.020). A shortfall between the predicted and clinically achieved expression of mesiodistal tooth movement with Invisalign was found for the anterior teeth after a mandibular incisor extraction. The number of aligners, duration of aligner wear, and specific attachment designs were not found to significantly influence the accuracy of the achieved mesiodistal tip movements. •Mandibular incisor extractions may be considered in clear aligner therapy.•The mesiodistal tip of teeth adjacent to extraction spaces impacts dental esthetics.•Clinically achieved mesiodistal tip was less than predicted for incisors (78.89%) and canines (54.16%).•However, mandibular incisors were less likely to move in the planned direction than canines.•Attachment designs did not influence outcomes.